2016
DOI: 10.1159/000443991
|View full text |Cite
|
Sign up to set email alerts
|

Left Adrenal Gland Analysis in Lung Cancer Patients Using the Endobronchial Ultrasound Scope: A Feasibility Trial

Abstract: Background: In lung cancer patients, the adrenal glands are predilection sites for distant metastases. Esophageal endoscopic ultrasound - fine-needle aspiration (EUS-FNA) is a minimally invasive and accurate method for left adrenal gland (LAG) analysis but requires a conventional gastrointestinal echoendoscope. Complete endobronchial and esophageal mediastinal nodal staging can be achieved by just a single endobronchial ultrasound (EBUS) scope, introducing it into the esophagus (EUS-B) following the endobronch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 26 publications
5
25
0
2
Order By: Relevance
“…Non-small cell lung cancer (NSCLC) accounts for 85% of lung cancer cases. Despite recent advances in diagnosis and treatment including surgery, chemotherapy, radiotherapy and targeted therapy, the prognosis of NSCLC patient remains poor [410]. It is necessary to identify new molecular markers involved in the regulation of lung cancer cell aggressiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Non-small cell lung cancer (NSCLC) accounts for 85% of lung cancer cases. Despite recent advances in diagnosis and treatment including surgery, chemotherapy, radiotherapy and targeted therapy, the prognosis of NSCLC patient remains poor [410]. It is necessary to identify new molecular markers involved in the regulation of lung cancer cell aggressiveness.…”
Section: Introductionmentioning
confidence: 99%
“…EBUS has remained an indispensable tool for the evaluation of crucial mediastinal stations in lung cancer staging, especially low paratracheal (4R and 4L), subcarinal (7), hilar (10R and 10 L), and interlobar (11R and 11L). A combination of EUS‐B and EBUS improves in‐depth staging of lung cancer with better patient tolerance and access to evaluate upper paratracheal stations (2R and 2L), the left lower paratracheal station (4L) and possibly the left adrenal gland by a single operator during one session . A recent study demonstrated that combined endosonography showed an increased sensitivity of 9% for N2/N3 disease in lung cancer staging compared to conventional PET‐CT‐targeted EBUS .…”
Section: Discussionmentioning
confidence: 99%
“…Surgery or radiotherapy with curative intent is advised in the case of localized disease. Imaging by CT and/or positron emission tomography should be obtained to characterize the primary lung lesion, the mediastinum, and to search for metastases, but additional tissue staging is frequently required to confirm or exclude metastatic involvement, for example if a lesion in the liver is suspected of malignancy [1,2,3,4,5,6]. …”
Section: Discussionmentioning
confidence: 99%
“…In recent years, chest physicians have started using an endoscope designed for endobronchial ultrasound (EBUS) in the esophagus (EUS-B) for detection and biopsy of lesions both above and below the diaphragm including the left adrenal gland [3,4,5]. However, EUS-B-FNA from a liver metastasis has never been described before.…”
Section: Introductionmentioning
confidence: 99%